Simple Measurements with Network Time Protocol for Teaching Time and Frequency Metrology - Sarafidis, Charalampos; Sfetsiou, Christina; Polatoglou, Hariton M. (2019 8th International Conference on Modern Circuits and Systems Technologies (MOCAST), 2019)
Metrology, the science of measurements and instrumentation, is a continuously advancing field and affects many aspects of modern world, from industry to everyday living. This affects the future working environment of science and engineering students. Metrology as a subject is offered in many higher education curricula. Time and frequency section is an area which can provide educational paradigms for many fundamental metrology concepts with conceptual connections to both scientific and real world concepts and applications. Network Time Protocol (NTP), the basic time synchronization protocol used to maintain synchronization between computers and other network stations through internet can serve as an educational tool in order to introduce the students into the basic concepts of time and frequency metrology. In this work a methodology for introducing advanced time and frequency concepts to under-graduate students which combines theory and experimentation is presented.